EFFECT OF EXERCISE ON THE BODY COMPOSITION OF ADULTS IN MOUNTAIN OF FIRE AND MIRACLES MINISTRY, ILORIN - Bakinde, Surajudeen Tosho; Ruth, Adeyeni Adesewa (Universitas Pendidikan Indonesia, 2022)
The manifestation of chronic cardiovascular diseases is increasing every day, especially among adults. This could result from an unhealthy lifestyle and some underlying health conditions associated with increased body fat. Therefore, the study was conducted to ascertain the effect of exercise on the body composition of adults in Mountain of Fire and Miracles Ministry, Ilorin. The experimental research design of one group pretest-posttest was adopted for the study. The study population consisted of all religious leaders from Mountain of Fire and Miracles Ministries, Ilorin. Twenty (20) participants were selected for this study through the Systematic Sampling Technique. Consent of the participants was sorted, and health screening of the participants was conducted. FITT principle was followed for a duration of 8-weeks of exercise intervention. Standardized instruments (bioelectrical impedance analysis, non-elastic tape-rule, portable height-scale) were used to collect body composition parameters (% body fat, WHR, BMI). Data were analyzed using descriptive statistics of frequency counts and percentages to describe their body composition.In contrast, inferential statistics of paired t-test was used to analyze the hypotheses formulated, adopting a p-value of 0.05 for statistical significance. The statistical package for social science (SPSS) software was used for data analysis. The findings revealed that a significant effect of exercise exists on the body mass index of adults in Mountain of Fire and Miracles Ministry, Ilorin. This study, therefore, concluded that there is a strong interaction between the body composition of adults and their physical activity level. It was recommended that there should be a frequent orientation on the need to participate in regular exercise to the general public.